Evaluation of Retinol, Cholecalciferol, α-Tocopherol and Phylloquinone levels in naturally infected calves with eimeriosis - Denizhan, V; Kozat, S; Ekin, S (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to evaluate whether serum vitamin A (retinol), vitamin D (cholecalciferol), vitamin E (α-tocopherol), and vitamin K (phylloquinone) levels changed in naturally infected calves with coccidiosis. The study was conducted on a total of 70 calves, 55 with coccidiosis and 15 healthy (control) calves of different races, sexes, and ages ranging from 26 to 60 days, with complaints of bloody diarrhea, weight loss and tenesmus. As a result of statistical analysis; serum vitamin A, D, E, and K concentrations of calves with coccidiosis were significantly lower than the control group (P<0.001). In the correlation between parameters in calves with coccidiosis; in Pearson correlation for calves with coccidiosis, between serum retinol (vitamin A), cholecalciferol (vitamin D), α-tocopherol (vitamin E), and phylloquinone (vitamin K) levels respectively; Positive correlation was detected at the levels of 0.996, 0.996, and 0.990. As a result; significant decreases were detected in serum retinol (vitamin A), cholecalciferol (vitamin D), α-tocopherol (vitamin E), and phylloquinone (vitamin K) levels concentrations of calves with coccidiosis. It can be thought that the use of preparations containing vitamin A, D, E, and K may be beneficial in addition to the routine treatments in cases of coccidiosis or other diarrhea.